Peningkatan Pengetahuan Penyakit Kecacingan pada Siswa Sekolah Dasar Negeri Kota Palembang - Karneli, Karneli; Karwiti, Witi; Hermansyah, Herry (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2020)
Health is a basic need for humans in general, one of the problems of Indonesian society both in rural and urban areas with inadequate hygiene and sanitation conditions is helminth infection. Worms are still a major health and economic problem in society, especially in people who do not keep themselves clean. It is estimated that around the world there are still as many as 300 million cases of helminthiasis, either single infestation or mixed infestation of worms. According to Gordon and Le Richt (1950) the emergence of a disease as stated by is largely determined by three main factors, namely the host (host), the cause of the disease (agent), and the environment (environment). that factor. If the main cause has been found, continue with efforts to overcome the cause in question, which in this case is to provide and organize health education efforts.